Phosphorylated proteins of the mammalian mitochondrial ribosome: implications in protein synthesis - Miller, Jennifer L. (2009)
Mitochondria, the powerhouse of eukaryotic cells, have their own translation machinery that is solely responsible for synthesis of 13 mitochondrially-encoded protein subunits of oxidative phosphorylation complexes. Phosphorylation is a well-known post-translational modification in regulation of many processes in mammalian mitochondria including oxidative phosphorylation. However, there is still very limited knowledge on phosphorylation of mitochondrial ribosomal proteins and their role(s) in ribosome function. In this study, we have identified the mitochondrial ribosomal proteins that are phosphorylated at serine, threonine or tyrosine residues. Twenty-four phosphorylated proteins were visualized by phosphorylation-specific techniques including in vitro radiolabeling, residue specific antibodies for phosphorylated residues, or ProQ phospho dye and identified by tandem mass spectrometry. Translation assays with isolated ribosomes that were phosphorylated in vitro by kinases PKA, PKCδ, or Abl Tyr showed up to 30% inhibition due to phosphorylation. Findings from this study should serve as the framework for future studies addressing the regulation mechanisms of mitochondrial translation machinery by phosphorylation and other post-translational modifications.